Bagong puso sa maogmang lugar (new heart in the happy place) a people-centered, IT-driven multi-use development - San Antonio, John Roi Dorutheo A.; Bo-ot, Luis Maria T. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
This thesis aimed to design a people-centered information technology center that integrates both existing and potential business model processes and serves as an effective catalyst development for an emerging central business district (CBD). The methodology employed in preparing this proposed project involved five phases, namely: identification of the locale, enumeration of issues, definition of the project, selection of the site and development of the project. The actual preparation of the project development plans was guided by the design elements and applications pre-identified for each design objective and programmatic goals. The programmatic goals included: hierarchy of users, exterior aesthetic, interior aesthetic, efficiency, creation of quality spaces, operation cost at minimum, and functional flexibility. In addition, the design philosophy adopted is inspired by Apple’s belief that ‘good designs involve empathy, focus and impute’. Finally, the proposed structure is characterized by attention to the following concepts: form follows function, less is more, spirit of place, efficiency, infusion, and tropical design.
includes appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Central business district -- Naga City